Phosphating process effluent treatment using activated carbon made from coco pod husk and custard apple seed. (2022) - Revathi, S.; Jeyanthi, J.; Suganya, R.
Abstract: Adsorption method is a cheaper way of treating industrial wastewater which has got considerable amount of heavy metals present in them. The discharge of phosphating process effluent from the subcontracting industry increases the eutrophication effect due to the decrease in dissolved oxygen to be present in the water. This study helps in obtaining an optimum dosage of activated carbon which can effectively remove the phosphate elements along with its base metal from the effluent without causing further turbidity in the waste water. Physical and chemical properties of the effluent are examined for (a) The raw effluent before it is treated and (b) Treated effluent using varying dosage of activated carbon.75 µm mesh was used for sieving the resultant activated carbon to obtain an uniform surface area over the adsorbent particles. Two mixtures are selected after adding activated carbon made from coco pod husk and custard apple seed in the ratio 1.1, 1:2, 1:3. Four different dosages are taken for studying the adsorption efficiency of the activated carbon mixture. 4 dosages were taken for analyzing the effect caused by different dosages under the following criteria; pH, Turbidity, Dissolved oxygen, Biological oxygen demand, Chemical oxygen demand, Total suspended solids and Total dissolved solids. Further the presence of Iron and Phosphate content is also determined to check for the adsorption efficiency of the adsorbent which was being used. In this project, 0.4 g/l was obtained as the optimum dosage of the mixture 1:3 at a temperature of 50 ℃ and at a contact time of 1.5 h. The adsorption efficiency for Iron and phosphate at optimum dosage were 91.66% and 95% respectively.